Diagnostic accuracy of the TsiogkaSpaeth grid test for detecting visual field defects in patients with glaucoma - George L Spaeth; Evangelia Samoli; Efthymios Karmiris; Anastasia Tsiogka; Klio I Chatzistefanou; Konstantina Koulotsiou; Vasileios Papastavrou; Georgios I Triantafyllopoulos; Dimitrios Papaconstantinou (BMJ Open Ophthalmology)
Background/aims To determine the accuracy of an innovative paper-based, low-cost, easily accessed, portable method of evaluating the visual field (VF).Methods Two groups of consecutive patients with glaucoma and controls were enrolled. Both eyes were assessed, and the Humphrey field analyser (HFA) (24-2) was used to identify patients with and without VF defects. The TsiogkaSpaeth grid (TS) grid test was performed in each eye of all participants. The Humphrey VF examination and the TS grid examination were conducted consecutively on the same day by two different examiners, prior to any other eye examinations. Sensitivity, specificity, and positive and negative predictive values of the TS grid scotoma area were assessed, using the results found with the HFA as the reference standard. A mixed-effects logistic regression model with a random intercept per participant was used to account for the correlation between eyes.Results This prospective, cross-sectional study recruited 51 participants in a tertiary care hospital-based glaucoma department. Of them, 19 had glaucomatous defects in both eyes, 12 had defects in 1 eye only and 21 had no defects in either eye. The sensitivity and specificity of the TS grid test were 81.63% (95% CI 68% to 91.2%) and 84.91% (95% CI 72.4% to 93.3%), respectively, positive predicted value was 83.33% (95% CI 69.8% to 92.5%) and negative predictive value was 83.33% (95% CI 70.7% to 92.1%). The area under the curve was 0.83 (95% CI 0.76 to 0.91). There was a significant correlation between the TS grid test score and the VF Index of the HFA 24-2 (r=0.87, p<0.0001) and the mean deviation of the HFA 24-2 (r=0.85, p<0.0001).Conclusions The TS grid test offers a reliable, low-cost alternative for VF examination in glaucoma patients. This method could be advantageous in clinical settings with limited access to traditional testing equipment. The TS grid has limitations, including difficulty of fixation loss testing and ensuring the correct fixation distance. The test’s self-administration reliability is uncertain, and some patients were unable to perform it. Other limitations concern the grid’s design and the small sample size of the study.